Financial development and economic growth nexus: A more revisionist approach. (8th April 2019) - Tsionas, Mike G.
Abstract: I provide extensions to Nyasha and Odhiambo regarding models of the finance—growth nexus. These models allow for heterogeneity, as well as mediation versus moderation effects of financial development. The conclusion is that useful models can be very different compared to what has been done in the literature.